Environmental, Social, and Governance (ESG) dan Implikasinya terhadap Keberlanjutan Keuangan Perusahaan - Jovan Febriantoko; Kartika Rachma Sari; Indriani Indah Astuti; Selimarsela; Adinda Annisa Avariza; Sabin Prastio (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2025)
Main Purpose - This study aims to analyze the effect of the Environmental, Social, and Governance (ESG) Score on financial performance and bankruptcy risk in banking and mining sector companies in Indonesia.Method - This research employs a quantitative approach using simple linear regression analysis to examine the relationship between ESG Score, financial performance, and bankruptcy probability. Secondary data were collected from annual and sustainability reports of companies listed on the IDX 2022–2023 period, with a total population and sample of 206.Main Findings - The ESG Score does not have an effect on any indicators of financial performance or bankruptcy risk. The corporate financial performance and stability are more strongly influenced by factors other than ESG. Theory and Practical Implications - The findings reinforce the Legitimacy Theory and Stakeholder Theory, suggesting that ESG serves primarily as a means of gaining social legitimacy rather than an economic driver. Policymakers, regulators, and corporations should strengthen ESG implementation through enhanced data transparency and sustainability incentives to ensure that ESG practices have a tangible impact on financial and business performanceNovelty - This study contributes by integrating a simultaneous examination of ESG Scores, profitability, and bankruptcy risk within the empirical context of Indonesia’s banking and mining sectors, an area that has received limited attention in previous research.